Oxytocin impedes the effect of the word blindness post-hypnotic suggestion on Stroop task performance - Parris, Benjamin A. (Oxford University Press, 2014)
The ability to enhance sensitivity to relevant (post)hypnotic suggestions has implications for creating clinically informed analogues of psychological and neuropsychological conditions and for the use of hypnotic interventions in psychological and medical conditions. The aim of this study was to test the effect of oxytocin inhalation on a post-hypnotic suggestion that previously has been shown to improve the selectivity of attention in the Stroop task. In a double-blind placebo-controlled between-subjects study, medium hypnotizable individuals performed the Stroop task under normal conditions and when they had been given a post-hypnotic suggestion that they would perceive words as meaningless symbols. In line with previous research, Stroop interference was substantially reduced by the suggestion in the placebo condition. However, contrary to expectations, oxytocin impeded the effect of the word blindness suggestion on performance. The results are explained in terms of the requirement for the re-implementation of the word blindness suggestion on a trial-by-trial basis and the need to sustain activation of the suggestion between trials. The findings contrast with a recent study showing a beneficial effect of oxytocin on sensitivity to (post)hypnotic suggestions but are consistent with findings showing a detrimental effect of oxytocin on memory processes.